Representasi Makna Kekerasan Verbal pada Kolom Komentar Media Sosial Instagram @Anastasyakh: Analisis Semiotik Roland Barthes - Hasan Sentosa Lukito; Muhammad Alfikri; Fakhrur Rozi (Comit: Communication, Information and Technology Journal, 2025)
This study aims to identify and analyze the representation of verbal violence in the comments section of the Instagram account @anastasyakh using a qualitative descriptive approach and Roland Barthes' semiotic analysis. Through this method, the research delves into the denotative and connotative meanings in comments that contain elements of verbal violence, objectification, and coarse sexual views towards the subject, Anastasya Khosasih. The analysis results indicate that these comments not only refer to the subject's physical attributes literally but also reveal demeaning and derogatory stereotypes, creating an unsafe and harmful digital environment. By elucidating the layers of meaning in these comments, this study provides deep insights into the negative impact of harsh and demeaning language in online interactions and underscores the importance of fostering a more respectful and safe communication environment on social media.